Advertisements

Question 5 : Factorize x 2 − y 2 − 6y − 9

Question 5: Factorize  x^{2}- y^{2}-6y-9

How to factorize ?

Solution:

 

Given expression is

 x^{2}- y^{2}-6y-9

 =x^{2}- (y^{2}+6y+9)

 =x^{2}- [ (y)^{2}+2(3)(y)+ (3)^{2})]

= (x)^{2} - (y+1)^{2}

= [x+y+1][x-y-1]

 

 


  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  

You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

All original content on these pages is fingerprinted and certified by Digiprove
Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert